Respuesta :

3-(2x-5)=-4(x+2)

We simplify the equation to the form, which is simple to understand
3-(2x-5)=-4(x+2)

Remove unnecessary parentheses
3-2x+5=-4*(x+2)

Reorder the terms in parentheses
3-2x+5=+(-4x-8)

Remove unnecessary parentheses
+3-2x+5=-4x-8

We move all terms containing x to the left and all other terms to the right.
-2x+4x=-8-3-5

We simplify left and right side of the equation.
+2x=-16

We divide both sides of the equation by 2 to get x.
x=-8
I hope this helps you



3-2x+5 < -4x-8


-2x+4x < -8-8


2x < -16


x < -8



(-8, -.......]
ACCESS MORE